SPECIAL EDUCATION AND ACCESSIBILITY IN LOCAL DEVELOPMENT: A HISTORICAL LOOK AND THE NEW PARADIGMS OF MODEL TO MATRIZ DE APOIO À EDUCAÇÃO ESPECIAL (MAEE – MODEL TO SPECIAL EDUCATION SUPPORT) (Fiep Bulletin - online, 2012)
Centro Universitário Augusto Motta (UNISUAM - University Center Augusto Motta) developed and presented Matriz de Apoio à Educação Especial (MAEE – Model to Special Education Support), an unprecedented project in the State of Rio de Janeiro, created to support students with special needs by offering Training and Refresher Courses. This Model was designed according to Resolution #4 (2009), which established the Operational Guidelines for the Specialized Educational Service in Elementary Education, Special Education modality. This Project to Support the Improvement of Education in Public Schools in the State of Rio de Janeiro (2009) was approved by the Fundação de Amparo à Pesquisa do Estado do Rio de Janeiro (FAPERJ - Foundation for the Support to Research in the State of Rio de Janeiro) and was awarded a grant for research. It was carried out in the period between April 2010 and May 2011 at Instituto de Educação Carmela Dutra – IECD, a state institution located in Madureira, RJ. The project was developed on the belief of formation around the ideals of inclusion and citizenship, so dear to democratic culture, aiming at the goals of making UNISUAM a center of excellence and leadership in the Brazilian educational system, especially in regard to Special Education. So, eight Refresher and Qualifying Courses were taught. In 2012 MAEE project will be developed in private schools in and around the neighborhood of Bonsucesso, where that UNISUAM unit is located in Rio de Janeiro. The project aims at offering Refresher and Qualification Courses to its faculty members. Its main goals are education, production, distribution, support, production and research in Special Education.
Keywords: Model to Special Education Support; Refresher and Qualification Courses; Local Development; private schools